Islam, Sufism and everyday politics of belonging in South Asia - Dandekar, Deepra; Tschacher, Torsten (Taylor and Francis, 2016)
Cover -- Half Title -- Title Page -- Copyright Page -- Table of Contents -- List of figures -- Preface -- Note on transliteration -- List of contributors -- Introduction: Framing Sufism in South Asian Muslim politics of belonging -- Muslim politics of belonging -- Sufism: label, concept, name -- Sufism, shrines and the political: a contradiction in terms? -- The chapters in this volume -- Notes -- PART I: Producing and identifying Sufism -- 1. Sufis, dervishes and Alevi-Bektas¸is: Interfaces of heterodox Islam and nationalist politics from the Balkans, Turkey and India
Description based upon print version of record
Keywords: Electronic books; Aufsatzsammlung; Sufismus; Südasien